A certificação de produtos orgânicos como instrumento de inclusão social e econômica de agricultores familiares - Chollet, Camila Bonemann (2012)
The demand for organic products currently on the market is growing because consumers are showing a growing concern about the quality of food consumed. This tendency is found in different countries, pointing first concern with issues related to health and its link to food security, especially with regard to contamination by pesticides and other chemical agents. Then, aspects of the environment, organoleptic qualities, and also the concern not only with rural workers as well as animals are factors that drive consumption of organic products. This paper seeks to know the reality of an organic farmer in the region of Pelotas,RS, investigating the possible problems in the application of certification rules generated by the content of legislation and the relations between companies and this certification farmer. The instrument used to analyze the questions raised by this study was semi-structured questionnaire, which was applied to members of cooperatives farmers about organic farming. This work received as a result the local cooperatives tend to grow and meet the needs of farmers, making rules and regulations both economically and environmentally viable for farmers and for farmers who sell their products directly to the stamp fairs certification become is secondary. Since the law of the country still has many barriers that hinder the marketing of organic products, this study has identified support of cooperatives are fundamental to the process of organic farming. Therefore, this paper aims to create new public policies in favor of family farming organically, to increase the work done by local cooperatives, because this is one of the pillars of sustainability championed by, and is being done, even with difficulties associated with this group of.